Exploring factors which influence effective use of robotic process automation for business continuity in a South African bank - Phage, Mafutsana Keitumetse (University of the Witswatersrand, Johannesburg, 2023)
Technology advancement improves the organisation's operations while exposing them to risks and disruptions that require mitigation. Business continuity enables organisations to maintain the continuity of critical business operations during disruption. Banks adopt Robotic Process Automation (RPA) to achieve operational efficiency by automating repetitive and high-volume processes. South African banks are rapidly adopting RPA to streamline efficiency, maintain business continuity, and reduce operational costs to improve customer service. While many studies about RPA and business continuity exist, research on integrating these concepts is limited. This research explores determinants influencing RPA use for business continuity. It adopts an interpretivist paradigm combined with the Technology-Organisation-Environment (TOE) and Task-Technology Fit (TTF) framework as a theoretical lens. This theoretical lens proposes a TOE-TTF framework to explore factors affecting RPA use for business continuity. An exploratory research design applying a case study strategy and a purposive sample of ten participants was used in this study. Research data was collected in a South African bank using a semi-structured interview strategy. The results posit that critical TOE components are technological context (i.e., RPA process selection, compatibility, RPA stability and availability, and RPA monitoring, support, and stability), organisational standpoint (i.e., collaboration amongst stakeholders, top management support and business-led initiative) and environmental context (i.e., customer satisfaction, competition pressure, and regulatory requirements) substantially impacted RPA use for business continuity. Also, bank's legacy systems strongly influence RPA use for business continuity. TTF theory factors, namely task, fit, utilisation, and performance factors, influenced RPA use for business continuity. This research provides a unique contribution as it integrates RPA and business continuity notions with the TOE-TTF framework viewpoint in a South African bank advancing the IS discipline. The results provide practitioners and researchers with a better understanding and identify critical factors organisations can be considered when using RPA for business continuity in banking. South African banks could illustrate beneficial insights when facing more competition and evolving customer needs and requirements. The research findings could be used for other technologies that are intended to be used for business continuity in different sectors.
Master’s Thesis Submitted in fulfillment of the requirements for the degree of Master of Commerce by Research in the field of Information Systems
Keywords: UCTD; Robotic Process Automation; Business continuity; Technological Organisation Environmenta; Task-Technology Fit; South Africa; SDG-8: Decent work and economic growth